Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.3389/fimmu.2020.01432
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Proteomic Profile of Psoriatic Epidermis Identifies OAS2 as a Novel Biomarker for Disease Activity

Abstract: Psoriasis is a common chronic inflammatory systemic disease. Epidermal proteins are considered to be important in maintaining skin barrier function, innate immunity, and inflammation. To define more possible roles of the epidermis in the pathogenesis of psoriasis, quantified proteomic analysis was used to screen and analyze the differentially expressed epidermal proteins between 16 psoriasis patients and 15 healthy controls. Upregulated differential expression proteins (DEPs) include several significant functi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 37 publications
0
29
0
Order By: Relevance
“…MX2 is a cytokine induced by interferon IFN-α, which resists viral infection by inhibiting the accumulation of viral nuclear DNA ( 50 , 51 ). As a new potentially sensitive biomarker, OAS2 is significantly up-regulated in psoriasis, a chronic inflammatory systemic disease, and can predict the severity and activity of the disease ( 52 ). The antiviral protein IFIT2 was found to be an important limiting factor for rabies virus, which can directly or indirectly resist virus replication ( 53 ).…”
Section: Discussionmentioning
confidence: 99%
“…MX2 is a cytokine induced by interferon IFN-α, which resists viral infection by inhibiting the accumulation of viral nuclear DNA ( 50 , 51 ). As a new potentially sensitive biomarker, OAS2 is significantly up-regulated in psoriasis, a chronic inflammatory systemic disease, and can predict the severity and activity of the disease ( 52 ). The antiviral protein IFIT2 was found to be an important limiting factor for rabies virus, which can directly or indirectly resist virus replication ( 53 ).…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies found that increased expression of NFAT5 was involved in inflammatory and autoimmune diseases ( Choi et al, 2017 ; Choi et al, 2018 ). OAS2 is a potential new sensitive biomarker, which can predict the activity and severity of psoriasis, and can evaluate the clinical treatment efficacy ( Zhou et al, 2020 ). OAS2 can also be considered as biomarker gene for systemic lupus erythematosus (SLE) diagnosis ( Fang et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Besides POSTN, a secreted extracellular matrix protein originally derived from the osteoblasts, was believed as a potential serum biomarker with a slightly higher concentration in PsA patients than in PsC patients ( 86 ). Another latest research using isobaric tags for relative and absolute quantitation (iTRAQ), a labeled MS technology, found 2-5-oligoadenylate synthase levels in both serum and psoriatic epidermis that were positively correlated with the severity of psoriasis through PASI and BSA ( 87 , 88 ). As some data suggest, severe psoriasis can account for another cutaneous feature with a higher risk and prevalence of psoriatic arthropathy.…”
Section: Proteomics In Potential Biomarker Discovery Of Psa Transitionmentioning
confidence: 99%